Development and implementation of a support programme for parents of youth abusing substances in selected Public Hospitals in Limpopo Province : a nursing leadership perspective - Hlahla, Lina Sebolaisi (My University, 2022)
It is in the parents’ interest to protect their youth and keep them away from substance abuse. It can be particularly disturbing for them to learn that their child abuses substances, or is an addict. When the youth abuses the substance, it is normal for parents to experience feelings of guilt and sadness. They also become angry; they may feel angry towards each other, the world at large or towards their youth. Stress levels can increase when caring for an addicted child. Parents who have youth abusing substances need support. The desire to get the correct and clear information about their child is one of the important needs of parents. They desire information and support about their child’s improvement during hospitalisation and post hospitalisation. The purpose of this study is to develop and implement a support programme for parents of youth abusing substances in selected public hospitals in Limpopo Province. The objectives were to explore and describe the experiences of parents of youth abusing substances; to describe the knowledge and practices of parents of youth abusing substances in caring for youth abusing substance; to identify the support needs of parents of youth abusing substances; to describe a conceptual framework for the development and implementation of a support programme for parents of youth abusing substances; to develop a support programme for parents of youth abusing substances and lastly to implement a support programme for parents of youth abusing substances in selected public hospitals in Limpopo Province. A mixed-method, exploratory sequential research design was used in this study to achieve the study aim. Fourteen participants consented to participate in the qualitative strand of the study while 169 participants consented to take part in the quantitative strand of the study. Tesch’s eight steps of data analysis were used to analyse qualitative data, data was analysed in a form of themes and sub-themes. SPSS version 26 was used to analyse quantitative data. Logistic regression and ANOVA test were used to calculate associations, odds ratios and means for knowledge The findings of this study indicate that the parents need support from the nurses which include the following: Knowledge and information sharing regarding substance abuse; Attention with regard to their own wellbeing as parents of youth abusing substances; Capacitation with better strategies and interventions to manage themselves while helping their youth with substance abuse disorders; Support by the nurses to the parents as the relatives of the patients which include debriefing on the patient’s condition, counselling, and referral to the relevant healthcare professionals. To support the parents of youth abusing substances the nurses need to continue with the implementation of the support programme. The Limpopo’s Department of Health may assist in allowing the in-service education for the nurses to support the parents of youth abusing substances. There should also be awareness programmes that are about substance abuse for the parents and the youth
Thesis (Ph.D. (Nursing Sciences)) -- University of Limpopo, 2022
Keywords: Support; Programme; Parents; Youth; Substances; Abuse; Substance abuse -- South Africa -- Limpopo; Drug addiction -- South Africa -- Limpopo; Parents -- Alcohol use; Hospitals; Nursing